Perancangan Arsitektur Sistem Informasi Terintegrasi Menggunakan TOGAF ADM di UIN Raden Fatah Palembang - Freddy Kurnia Wijaya; , Farah Hasywaza Audremayna; Tasya; Syarifah Rizqiyah (YAYASAN PADHANG MANAH SIBYAN, 2026)
The use of information technology in higher education often faces the challenge of system fragmentation. UIN Raden Fatah Palembang has nine service applications including PMB, SIMAK, SILAYAK, E-Learning, E-KKN, E-Skripsi, E-Guidance, Cek Plagiat, and Repository which currently operate in silos. This condition results in data redundancy and inefficient bureaucratic flows. This study aims to design an integrated information system architecture using the TOGAF ADM framework as the basis for developing the SIMA Portal. The research focuses on the Preliminary Phase to Phase C (Information Systems Architecture). At the architectural vision stage, the Single Source of Truth principle is established to ensure information consistency. The business architecture is designed to simplify bureaucracy through efficient BPMN modeling. Furthermore, the information system architecture produces an integrated Relational Data Model that connects data entities from nine application modules. The research results in an architectural blueprint that is able to eliminate obstacles to automatic data exchange through the Single Sign-On (SSO) mechanism. The implementation of this design is expected to improve operational efficiency and the quality of academic services through accurate and centralized data synchronization.